International Students' Cocurricular Involvement at a University in South Africa - Naik, Sapna; Wawrzynski, Matthew R.; Brown, Joelle (Journal of International Students, 2017)
Despite a growing body of literature on international student involvement, international students in the South African context have remained understudied. In this quantitative study, we examined international students’ cocurricular involvement and associated learning and development in a South African university. Participants included 198 international students who completed the Student Experiences Survey (SES). We found international students were generally highly involved and reported benefits and barriers to their involvement as well as a strong sense of belonging. Recommendations to better integrate international students into the university by minimizing barriers and increasing opportunities and learning in involvement are included for student affairs practitioners.